ENDOSCOPIC FINDINGS IN PATIENTS PRESENTING WITH OESOPHAGEAL DYSPHAGIA - Khan, Adil Naseer; Said, Khalid; Ahmad, Mukhtar; Ali, Kishwar; Hidayat, Rania; Latif, Humera (Journal of Ayub Medical College Abbottabad, 2014)
Background: Dysphagia is the difficulty in swallowing and is often described by the patients as a '˜perception' that there is an impediment to the normal passage of the swallowed material. It is frequently observed that there is an association of dysphagia with serious underlying disorders and warrants early evaluation. The current study aimed to determine the frequency of common endoscopic findings in patients presenting with oesophageal dysphagia. Methods: This cross-sectional descriptive study was carried out in the department of Gastroenterology, Ayub Medical College, Abbottabad, from October 2012 to April 2013. Consecutive patients with dysphagia were included in the study and were subjected to endoscopy. Results: A total of 139 patients presenting with dysphagia were studied, 81 (58.3%) were males and 58 (41.7%) were females. The mean age was 52.41±16.42. Malignant oesophageal stricture was the most common finding noted in 38 (27.3%) patients with 28 (73.7%) males and 23 (60.5%) patients among them were above the age of 50years. It was followed by normal upper Gastrointestinal (GI) endoscopy in 29 (20.9%) patients and reflux esophagitis in 25 (18.0%) patients. Schatzki's ring was present in 14 (10.1%) patients; benign oesophageal strictures in 12 (8.6%) patients while achalasia was noted in 7 (5.0%) patients. 14 (10.1%) patients had findings other than the ones mentioned above. Conclusion: Malignancies are a more common cause of dysphagia in our population and early diagnosis can result in proper treatment of many of these cases. Keywords: Endoscopy, dysphagia, malignancy, reflux esophagitis, Schatzki's ring, achalasia